Rice Crop Manager Vietnam: CGIAR Innovation Packages and Scaling Readiness (IPSR) Innovation Profile - Hung Nguyen Van (CGIAR System Organization, 2025)
RCM provides rice farmers in Mekong River Delta and Red River Delta with a crop and nutrient management guideline customized to the needs of an individual farmer. It uses a farmer’s answers to questions about their rice farming practices to automatically generate a rice crop management guideline aimed at increasing the farmer’s net income by an equivalent of USD100 per hectare per crop. Each guideline provides an actionable and unique recommendation, which matches the location-specific cropping practices and needs of a farmer. The guideline is provided to the farmer as a one-page printout.